2020
DOI: 10.2174/1570159x18666200807144530
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of the Double-Edged Impact of Arachidonic Acid- Derived Eicosanoids in the Neuroinflammatory Background of Depression.

Abstract: : Eicosanoids are arachidonic acid (AA) derivatives belonging to a family of lipid signalling mediators that are engaged in both physiological and pathological processes in the brain. Recently, their implication in the prolonged inflammatory response has become a focus of particular interest because, in contrast to acute inflammation, chronic inflammatory processes within the central nervous system (CNS) are crucial for the development of brain pathologies including depression. The synthesis of eicosanoids is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 130 publications
0
19
0
Order By: Relevance
“…Moreover, it was discovered that the acetylation of cyclooxygenase-2 (COX-2) by aspirin could lead to the transcellular biosynthesis of epi-lipoxins, the so-called aspirin-triggered lipoxins (AT-LXA4), which are LXA4 analogs. Lipoxin expression was identified in neural stem cells, neurons, astrocytes, and microglia [ 28 , 29 ] The release of LXA4 under physiological brain conditions is limited, while its synthesis is upregulated under pathological stimulation [ 30 , 31 , 32 ]. The data available thus far have demonstrated that LXA4 and its analog AT-LXA4 are biologically active with mostly anti-inflammatory and pro-resolving profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was discovered that the acetylation of cyclooxygenase-2 (COX-2) by aspirin could lead to the transcellular biosynthesis of epi-lipoxins, the so-called aspirin-triggered lipoxins (AT-LXA4), which are LXA4 analogs. Lipoxin expression was identified in neural stem cells, neurons, astrocytes, and microglia [ 28 , 29 ] The release of LXA4 under physiological brain conditions is limited, while its synthesis is upregulated under pathological stimulation [ 30 , 31 , 32 ]. The data available thus far have demonstrated that LXA4 and its analog AT-LXA4 are biologically active with mostly anti-inflammatory and pro-resolving profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Although the acute inflammatory response is protective, dysfunction of its resolution and failure to return to tissue homeostasis lead to tissue damage and chronic inflammation [ 3 , 4 , 5 ]. Recently, the resolution of inflammation (RoI) was shown to be regulated by specialized pro-resolving mediators (SPMs) [ 6 , 7 ] that are enzymatically derived from essential polyunsaturated fatty acids, including arachidonic acid, eicosapentaenoic acid and docosahexaenoic acid, in a lipoxygenase-dependent manner [ 8 , 9 ]. SPMs exert their biological actions by binding to and activating cognate receptors, of which formyl peptide receptor 2 (FPR2) is of special interest [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclooxygenase (COX), lipoxygenase (LOX), Cytochrome P450 (CYP450) and other enzymes catalyze the formation of eicosanoid family of mediators, including thromboxanes (TXs), prostaglandins (PGs), leukotrienes (LTs), hydroxy eicosatetraenoic acid (HETE), which are closely related to the regulation of the in ammatory process (13,14). Once an imbalance of pro-in ammatory and anti-in ammatory shows in the central nervous system, diseases including depression may appear (15,16). In our study, plasma contents of AA and its downstream stable pro-in ammatory product, TXB 2 in MDD patients increased signi cantly compared with healthy controls, and then showed a downward trend after treatment, and their relative levels were positively correlated with the subjects' HDRS-17 score.…”
Section: Discussionmentioning
confidence: 99%